2005
DOI: 10.1537/ase.040303
|View full text |Cite
|
Sign up to set email alerts
|

A multivariate examination of the Hexian calvaria

Abstract: The Homo erectus calvaria from Hexian, Anhui province, China is an important component of the fossil sample from East Asia. This specimen is the most complete Chinese H. erectus cranium found outside Zhoukoudian. Previous work has shown that the fossil crania from Zhoukoudian exhibit a unique metric pattern not seen in specimens from Africa or Indonesia. Multivariate statistics that assess the statistical significance of distances have not been used to compare the Hexian cranium to other relevant fossils, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…Instead, some researchers in support of the regional continuity of the morphologies of the Chinese fossil record [5] , [7] , [8] were inclined to emphasize the similarities of the Hexian and Zhoukoudian V skulls, particularly in relation with some advanced features that, according to them, were not detected on the skulls recovered from the lower layers of Zhoukoudian Locality 1. Nevertheless, recent multivariate analyses on cranial metrical variation in East Asia during the Early and the mid-Middle Pleistocene periods pointed out that the Hexian skull was clearly differentiated from the specimens found in Zhoukoudian Locality 1, including skull V [9] . In the present study, we have also revealed several metrical and morphological differences when comparing the teeth from Hexian and Zhoukoudian Locality 1.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, some researchers in support of the regional continuity of the morphologies of the Chinese fossil record [5] , [7] , [8] were inclined to emphasize the similarities of the Hexian and Zhoukoudian V skulls, particularly in relation with some advanced features that, according to them, were not detected on the skulls recovered from the lower layers of Zhoukoudian Locality 1. Nevertheless, recent multivariate analyses on cranial metrical variation in East Asia during the Early and the mid-Middle Pleistocene periods pointed out that the Hexian skull was clearly differentiated from the specimens found in Zhoukoudian Locality 1, including skull V [9] . In the present study, we have also revealed several metrical and morphological differences when comparing the teeth from Hexian and Zhoukoudian Locality 1.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies of cranial morphology strongly suggest that Javanese H. erectus during and after the late Early Pleistocene formed a continuously evolving population lineage that was effectively independent of the H. erectus populations of northern China (Antón, 2002;Baba et al, 2003;Durband et al, 2005). If crown size reduction was a continuing trend in later Javanese H. erectus during the Middle/Late Pleistocene, like in those cases recognized in various regional groups of archaic Homo in Africa, Europe, and China (Zhang, 1991;Bermúdez de Castro and Nicolas, 1995;Bräuer and Schúltz, 1996;Kaifu et al, 2005b), it is likely that Javanese H. erectus was not ancestral to Australian Aborigines.…”
Section: Discussionmentioning
confidence: 99%
“…Hominin fossils, including a left mandibular corpus (PA 831), found at the Hexian site in Eastern China, have been dated to 412 ± 25 ka (Grün et al, ) (see Hexian site and discovery of the hominin mandible section for more details). The fossil assemblage from Hexian also includes a skull and isolated teeth that have been systematically described and compared (Durband, Kidder, & Jantz, ; Huang, Fang, & Ye, ; Wu, Schepartz, Falk, & Liu, ; Xing et al, ). Apart from very preliminary descriptions and comparisons (Huang et al, ; Huang, Fang, & Ye ; Wu & Dong, ), the Hexian mandible's morphology and evolutionary context within the East Asian Middle Pleistocene has not been studied.…”
Section: Introductionmentioning
confidence: 99%